COMPARISON BETWEEN CHEMICAL AND MINERALOGICAL PROPERTIES OF OAK FOREST AND BARE CULTIVATED SOILS IN IRAQI KURDISTAN REGION - & et al., Abdullah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted during 1/7/2016 to 20/12/2018, which aimed to determine chemical and mineralogical properties of oak forest and bare cultivated soils at 6 locations  in Iraqi Kurdistan region, the samples were collected from two depths (0 – 30) and (30 – 60) cm. The study included some chemical and physical properties and identification of clay minerals from X-ray diffraction data. Peak height is used as a rough indicator of relative abundance of minerals. In general, the expansion of 14°A to ≈ 17°A in ethylene glycol treatment was not detected because measuring started from 5θ so that’s why we cannot differentiated between Chlorite and Semectite in that treatment. The main results indicated that the organic matter, clay content and CEC values in forest soils were higher than their values in bare cultivated soils, swelling chlorite being the dominant mineral in these soils. While the miner clay mineral at that locations were Kaolinite. Mica was identified at all location, while the dominant type of Mica at forest soils was Muscovite which was obtained from 4 Locations, while Mica Biotite was dominant in bare cultivated soils which was obtained from 4 sites.